2001
DOI: 10.1103/physreve.64.060302
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of a confined granular material

Abstract: We study the rheology of a granular material slowly driven in a confined geometry. The motion is characterized by a steady sliding with a resistance force increasing with the driving velocity and the surrounding relative humidity. For lower driving velocities a transition to stick-slip motion occurs, exhibiting a blocking enhancement whith decreasing velocity. We propose a model to explain this behavior pointing out the leading role of friction properties between the grains and the container's boundary. . Anot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 24 publications
7
45
1
Order By: Relevance
“…On the other hand, it is also known that aging occurs at the contacts between the particles [5], which manifests itself as a logarithmic increase of the friction coefficient between grains as a function of time. It could also be responsible for the observed slow dynamics, as has been suggested in experiments by Ovarlez et al and Nasuno et al [6,7], which show rate dependence and slow strengthening characteristics of aging at the interparticle contacts, respectively.The goal of this Letter is to demonstrate the existence of slow relaxation in the response of dense granular matter to infinitesimal strain perturbations and to elaborate on the origin of the dynamics. The experiments reveal a very slow stress relaxation under a constant applied differential strain.…”
mentioning
confidence: 55%
“…On the other hand, it is also known that aging occurs at the contacts between the particles [5], which manifests itself as a logarithmic increase of the friction coefficient between grains as a function of time. It could also be responsible for the observed slow dynamics, as has been suggested in experiments by Ovarlez et al and Nasuno et al [6,7], which show rate dependence and slow strengthening characteristics of aging at the interparticle contacts, respectively.The goal of this Letter is to demonstrate the existence of slow relaxation in the response of dense granular matter to infinitesimal strain perturbations and to elaborate on the origin of the dynamics. The experiments reveal a very slow stress relaxation under a constant applied differential strain.…”
mentioning
confidence: 55%
“…These experiments span a vast range of lengths, and include studies at the atomic [14], lab [7,8,11,12,13], and geological scale [9,10]. Recent experiments by Ovarlez et al [6] using granular materials sliding against the interior wall of a piston showed clear rate dependence that was associated with aging effects of individual solid-friction contacts and with the force network. Additionally, experiments by Nasuno et al [7,8] in which a solid surface was pushed across a granular bed showed a slow strengthening (or aging) with time of the (quasi-static) force.…”
mentioning
confidence: 99%
“…In granular materials, rate dependence may occur because of slow formation of capillary bridges, due to slow condensation with characteristic times of several minutes [39,40,111], or viscous transport of the liquid across the pores network [80,189] through ~ 100-nm-thick wetting films on micron-sized grains. However, in the experimental time scale, bridge evolution in the CC would not explain the viscous behavior.…”
Section: P-h Curvesmentioning
confidence: 99%
“…Although the continuous phase in these media is formed, in principle, only by a gas (air, mostly), it virtually always involves some amount of liquid, frequently due to the mere adsorption of water from the moist surrounding. For example, the important influence of humidity in the mechanical behavior of powders and granular media exposed to habitual atmospheric conditions [e.g.−, 38,39,40,41] shows that water must be almost universally considered. Thus knowing its interaction with particles is essential for e.g.…”
Section: Introductionmentioning
confidence: 99%